Direct and indirect effects of new businesses on regional employment: an empirical analysis - Michael Fritsch; Florian Noseleit; Yvonne Schindele (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
We analyze different types of effects that new businesses may have on regional employment. We introduce different measures for employment change by separating employment change in incumbent businesses and employment change in new businesses. There are pronounced differences between regions with regard to the different employment effects. The average indirect employment effects of new business formation on incumbent employment are positive and are considerably larger than the employment that is directly generated in the new businesses.
Keywords: L26; M13; O1; O18; R11; 330; Entrepreneurship; new business formation; regional development; direct and indirect effects; Unternehmensgründung; Unternehmensentwicklung; Beschäftigungseffekt; Regionale Entwicklung; Deutschland